2003
DOI: 10.1016/s0002-9270(03)00241-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of fresh frozen plasma infusion in correction of coagulopathy of chronic liver disease: a dual phase study

Abstract: Our results reiterate previous observations made more than 45 yr ago, that fresh frozen plasma infusions using the number of units commonly employed in clinical practice infrequently correct the coagulopathy of patients with chronic liver disease. Higher volumes (6 or more units) may be more effective but are rarely employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 0 publications
2
71
0
1
Order By: Relevance
“…Not only do these published results suggest that INR may not accurately predict those at high risk of bleeding, but there is also little evidence to suggest that correction of INR by administration of FFP has any beneficial clinical effect 12,13 . Consequently, the potential risk and significant cost associated with blood product transfusion may be avoided in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do these published results suggest that INR may not accurately predict those at high risk of bleeding, but there is also little evidence to suggest that correction of INR by administration of FFP has any beneficial clinical effect 12,13 . Consequently, the potential risk and significant cost associated with blood product transfusion may be avoided in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of FFP infusions is usually either to improve the coagulopathy before invasive procedures or to control ongoing bleeding from various sites in patients with vitamin K-unresponsiveness prolonged prothrombin time. The mean prothrombin time was improved by the infusion of 2–6 units of FFP, but only 12.5% of the retrospective study group and 10% of the prospective study groups showed reversal of their coagulopathy, and higher volume (6 or more units) may be more effective but rarely is employed [96]. However, attention should be directed to complications including the risk of infection, allergic reaction, and acute volume expansion leading to heart failure or pulmonary edema [95, 96].…”
Section: Possible Therapeutic Approaches Of Adamts13 Supplementatimentioning
confidence: 99%
“…Fresh frozen plasma and platelets (particularly for a platelet count <50,000 mL-1) have often been used to correct coagulopathy. These measures do not adequately correct the coagulopathy, and could potentially induce volume overload and rebound portal hypertension 31 . The use of recombinant factor VII has been shown to improve hemostasis rates, but it does not improve survival 32 .…”
Section: Assesement Of Severity Of the Bleedingmentioning
confidence: 99%